Quality Assessment of Vannamei Shrimp from Indonesian Waters: Quality Assessment of Vannamei Shrimp - Nurhayati, Tati; Kustiariyah; Jacoeb, Agoes Mardiono; Utari, Sonya Ayu; Azizah, Laela Hidayatul; Hidayat, Taufik (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
The special feature that indicates quality degradation in shrimp is the existence of blackspot. The spreading rate of blackspot on shrimp will grow in line with the storage time, thus it can be used as a parameter on quality assessment of shrimp deterioration.. This study aims to determine the quality of shrimp during chilling storage in organoleptic, histology, and enzymatic. The procedure of this study includes sampling, observations, organoleptic test, histological analysis, observing polyphenoloxidase and cathepsin activity. The results showed that pre-rigor phase on shrimp occurs shortly after the death (storage 0 d to 2 d), rigor mortis occurs on 3 d to 11 d of storage, postrigor occurs on day 12 d to 17 d of storage, and deterioration (decay) occurs on the 18 d of storage until 23 d. Early appearance of blackspot appeared in cephalothorax and continues over time. Muscle fibers in pre- rigor phase has not been damaged. Muscle fibers still looks compact and solid. Muscle fibers in rigor mortis phase begins to experience shrinkage. Muscle fibers in post rigor phase had been cut into pieces. Cathepsin was most active on rigor mortis phase.